A proposal of strategies for DBS Securities Philippines, Inc. (DBSSP) - Tan, Rose Mary L. (Animo Repository, 1998)
The Philippine stock market is considered one of the oldest in Asia. The Securities and Exchange Commission granted the Philippine Stocks Exchange, Inc. its license to operates as a securities exchange on 4 March 1994. It simultaneously canceled the license of the Manila Stock Exchange and Makati Stock Exchange. Membership of the PSE is limited to 200 with each member entitled to one seat. This can be acquired through direct purchased from the exchange or from existing member. Member must also behave to keep a minimum subscribed capital stock in such amount as may be required by the board of governors, but also less than the minimum amount as may be required by law or regulations. To identify the key structural features that determine industrys profitability, Porters model for five basic competitive forces will be used. There is the presence of a high threat of entry. Membership can be acquired through direct purchase from the exchange or from an existing member. The barriers to entry as follows: New entrants, particularly foreign brokers, are forced to come in at large scale. For a corporation wishing to become a member, it has to have a minimum unimpaired capital of P 10 million, exclusive of the value of the membership seat. Current cost for a seat in Philippine Stock Exchange ranges between P65 million to P 90 million. The intense rivalry within the industry is due to numerous competitors. There are 185 active brokers in the industry. There is a high pressure from substitute products. Brokers are being increasingly confronted with such substitute as real estate, insurance, money market, time deposits, investments that earns higher interests and lesser risk to invest capital, accentuated in performance by the poor performance of the equality market. Clients of brokers compete with the industry by forcing down commission rates, bargaining for higher quality investment strategies or more services, and playing competitors against each other. There is an absence of a supplier group in the securities industry by forcing down commission rates, bargaining for higher quality of investment strategies or more services, and playing competitors against each other. There is an absence of a supplier group in the securities industry.